Wellness comes in salty water: Thalassotherapy spas and service level of satisfaction - Rodrigues, H. (2022)
The lucrative and rapid expansion of the wellness tourism sector in Europe and Asia has led to intense competition among wellness tourism destinations. This study investigates the business in five major nations: China, Japan, Russia, Germany, and Italy, which together accounts for 77% of global revenue pre-pandemic from the thalassotherapy spas and resort industry. We analysed TripAdvisor’s 3116 tourists’ review responses representing five-star thalassotherapy facilities. The primary drivers of an excellent service include hotel room facilities and thalasso-treatments with seawater. We identify a semantic clustering linked to thalassotherapy spa attractiveness and determine attributes that are pertinent to satisfaction of wellness-seeking tourists. The current study contributes to the sparse literature on wellness tourism specifically relating to thalassotherapy spas and the level of satisfaction associated with the service. The study suggests practical advice to address the negative effects of customer dissatisfaction on services that can overshadow the positive effects of satisfaction.